Effect of genotyping on the severity of rotavirus Gastroenteritis - Chandrasena, T.G.A.N.; Rajindrajith, S.; Gunawardena, N.K.; Silva, G.M.K.S.; Pathmeswaran, A.; Kazuhiko, M.; Kamruddin, A. (Sri Lanka College of Paediatricians, 2011)
INTRODUCTION: Rotavirus is the commonest cause of paediatric gastroenteritis. There remains a controversy regarding disease severity being related to rotavirus genotype G9. OBJECTIVE: Study the genotype related severity of rotavirus gastroenteritis. DESIGN, SETTING AND METHOD: All children under 5 years of age who were admitted with acute diarrhoea to North Colombo Teaching Hospital and submitted a sample of stool for analysis from April 2005 to October 2008 were selected for the study. Clinical information was collected regarding the study group. Acute diarrhoea was defined as passage of 3 times or more stools over a period of 24 hours. Stools were collected from cases with blood and mucus diarrhoea as well. The stool compliance rate was around 75-80%. Faecal specimens were tested and genotyped for rotavirus using the ELISA kit, Rotaclone® (Meridian Diagnostics, Cincinnati) and reverse transcription (RT) PCR respectively. Severity of gastroenteritis was assessed using the 20 point scoring system ofVesikariand Ruuska. RESULTS: The total number of stool specimens collected during the study period was 813 and of this 178 were positive for group A rotavirus; all the rotavirus positive stool specimens were genotyped. The two predominant VP7 genotypes were G9 (76; 42.7%) and Gl (35; 19.7%) followed by G2 (22; 12.4%), G3 (22; 12.4%), G12 (18; 10.1%) and G4 (4; 2.2%) respectively. The mean severity scores of, Gl, G2, G3, G4, G9 and G12 were 12,12,12,14,13 and 13, respectively. Comparison of clinical features between the two common G types, G9 and Gl revealed the following: duration of diarrhoea was longer among G9 (mean 4±2 days) than Gl (mean 2±1 day) and a higher percentage of cases were febrile and had vomiting in G9 (84.9 and 86.3 respectively) than Gl (76.7 and 65.5 respectively) infections (p>0.05). The rest of the clinical features were similar. The percentage with severe disease (score >14) was higher among the G9 (38.4) than among Gl (26.7) infections (p>0.05). CONCLUSION: Although rotavirus G9 genotype was associated with a more severe gastroenteritis than the common Gl genotype, this association was not significant (p>0.05).
Abstract of Free Papers (FP 07) - The 14th Annual Scientific Congress of the Sri Lanka College of Paediatricians, 27th-30th of July, 2011, Hotel Galadari, Colombo
Keywords: geimotyping